2019
DOI: 10.1371/journal.pone.0223688
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating optical field directed hierarchical self-assembly of homogenous versus heterogeneous nanoclusters with femtosecond optical tweezers

Abstract: Insights into the morphology of nanoclusters would facilitate the design of nano-devices with improved optical, electrical, and magnetic responses. We have utilized optical gradient forces for the directed self-assembly of colloidal clusters using high-repetition-rate femtosecond laser pulses to delineate their structure and dynamics. We have ratified our experiments with theoretical models derived from the Langevin equation and defined the valid ranges of applicability. Our femtosecond optical tweezer-based t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…Not only optical trapping potential but also assembly of NPs can be controlled by femtosecond laser polarization. , Two-photon fluorescence is used for tracking the movement of individual NPs and for analyzing their geometry . Even the hierarchical self-assembly was demonstrated and discussed, which will be a useful reference for fabricating the assembly as the bottom-up approach. The different optical trapping conditions are applied in the present work and their study: at the solution interface vs in solution, by CW vs by the femtosecond laser, for bare vs for dye-doped particles, and in the ensemble level vs the individual particle level, but it is important how laser polarization determines the respective phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only optical trapping potential but also assembly of NPs can be controlled by femtosecond laser polarization. , Two-photon fluorescence is used for tracking the movement of individual NPs and for analyzing their geometry . Even the hierarchical self-assembly was demonstrated and discussed, which will be a useful reference for fabricating the assembly as the bottom-up approach. The different optical trapping conditions are applied in the present work and their study: at the solution interface vs in solution, by CW vs by the femtosecond laser, for bare vs for dye-doped particles, and in the ensemble level vs the individual particle level, but it is important how laser polarization determines the respective phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…53,54 Twophoton fluorescence is used for tracking the movement of individual NPs and for analyzing their geometry. 55 Even the hierarchical self-assembly was demonstrated and discussed, 56 which will be a useful reference for fabricating the assembly as the bottom-up approach. The different optical trapping conditions are applied in the present work and their study: at the solution interface vs in solution, by CW vs by the femtosecond laser, for bare vs for dye-doped particles, and in the ensemble level vs the individual particle level, but it is important how laser polarization determines the respective phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…The other is the structuring of NPs will be more controllable by laser power and polarization. For example, Goswami et al demonstrated for different configurations of a few 250 nm PS NPs by utilizing femtosecond laser in solution. This interesting trial enables individual arrangement in NP assembly at the solution surface and interface too.…”
Section: Resultsmentioning
confidence: 99%
“…They manipulated dye‐doped 250 nm PS NPs and constructed a specific 3D geometry, [78,79] where two‐photon fluorescence is used for tracking the movement of individual NPs and for analyzing their geometry [80] . Even hierarchical self‐assembly was demonstrated and discussed, [81] which will be a useful reference for fabricating the assembly as the bottom‐up approach. They reported that not only optical trapping potential shape but also the assembly of NPs can be controlled by femtosecond laser polarization.…”
Section: Summary and Perspectivementioning
confidence: 99%